Family Dynamics and the Alzheimer's Disease Experience. (May 2021) - Esandi, Nuria; Nolan, Mike; Canga-Armayor, Navidad; Pardavila-Belio, M. Idoia; Canga-Armayor, Ana
Using constructivist grounded theory, this study explored how family groups respond to Alzheimer's disease in its early stages. Seven family units ( N = 22) participated in a series of 26 longitudinal interviews and 14 other family caregivers took part in three focus groups at a later stage for refinement and verification of the findings. Data analysis revealed four types of family dynamics: close dynamics at the start that were maintained throughout the experience, close dynamics at the start which became conflicting, conflicting dynamics at the start which remained problematic, and conflicting dynamic at the start which became closer over time. Factors such as prior relationships and family history, motivation to care, family organization, communication, and the family vision for future shaped the development of these dynamics. This theory of family dynamics in Alzheimer's disease has the potential to inform the development of more adequate early interventions for families living with the illness.